2022
DOI: 10.1038/s41598-022-18658-y
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes prevalence and risk factors, underestimated without oral glucose tolerance test, in rural Gombe-Matadi Adults, Democratic Republic of Congo, 2019

Abstract: An increase in the diabetes prevalence is reported worldwide. We aimed to determine the diabetes prevalence and its risk factors among adults in a rural area of the Democratic Republic of Congo. A cross-sectional study was conducted in 1531 inhabitants, selected by five stages, in the Health Zone of Gombe-Matadi. Diabetes was defined according to the American Diabetes Association and the International Diabetes Federation. Fasting glycemia and/or an oral glucose tolerance test were collected. We measured body m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Thus, Katchunga B.P et al reported a significant increase in both overall obesity and abdominal obesity in the general population of the East of the DRC, from 7.9% to 9.8% and from 12.6% to 14.6%, respectively [18]. Similarly, Muyer M. T at al noted an increase in the prevalence of diabetes mellitus from 4.0% in 2012 [19] to 5.3% in 2019 [20] [21] associated with insulin resistance and compensatory hyperinsulinemia [3].…”
Section: Discussionmentioning
confidence: 95%
“…Thus, Katchunga B.P et al reported a significant increase in both overall obesity and abdominal obesity in the general population of the East of the DRC, from 7.9% to 9.8% and from 12.6% to 14.6%, respectively [18]. Similarly, Muyer M. T at al noted an increase in the prevalence of diabetes mellitus from 4.0% in 2012 [19] to 5.3% in 2019 [20] [21] associated with insulin resistance and compensatory hyperinsulinemia [3].…”
Section: Discussionmentioning
confidence: 95%
“…We used G*Power software to calculate the required sample size for our study. Based on the following assumptions: a significance level (alpha) of 0.05, size effect of 0.1, a statistical power of 95%, and a prevalence of undiagnosed diabetes mellitus at 58.8% [ 24 ], the minimum required sample size was computed to be 304 participants. The target population for this study comprised apparently healthy individuals residing in Saudi Arabia, including both Saudi and non-Saudi nationals.…”
Section: Methodsmentioning
confidence: 99%
“…5 6 The factors associated with diabetes were being male, aged ≥ 40 years, general and abdominal obesity associated with the elderly, family history of diabetes, and hypertension. 6 Glycaemic control is the cornerstone of diabetes management, as it delays the occurrence of complications, reduces the cost of care and improves patient quality of life. Nevertheless, the control of diabetes remains a worldwide issue, with only about 50% of the patients living with type 2 diabetes controlled.…”
Section: Intrdoductionmentioning
confidence: 99%
“…3 4 In the Democratic Republic of the Congo (DRC), the prevalence of diabetes is estimated to be 5.8% for adults aged 20 to 79 years, 4 with a high proportion of persons living with diabetes in urban areas and the western part of the country. 5 6 The factors associated with diabetes were being male, aged ≥ 40 years, general and abdominal obesity associated with the elderly, family history of diabetes, and hypertension. 6…”
Section: Intrdoductionmentioning
confidence: 99%
See 1 more Smart Citation